PD-1 Blockade During Post-partum Involution Reactivates the Anti-tumor Response and Reduces Lymphatic Vessel Density - Tamburini, Beth A. Jirón; Elder, Alan M.; Finlon, Jeffrey M.; Winter, Andrew B.; Wessells, Veronica M.; Borges, Virginia F.; Lyons, Traci R. (Frontiers in Immunology, 2019)
Postpartum breast cancer patients, or breast cancer patients diagnosed within 10 years of last childbirth, are ~3-5 times more likely to develop metastasis in comparison to non-postpartum, or nulliparous, patients. Additionally, postpartum patients have increased tumor-associated lymphatic vessels and LN involvement, including when controlled for size of the primary tumor. In pre-clinical, immune-competent, mouse mammary tumor models of postpartum breast cancer, tumor growth and lymphogenous tumor cell spread occur more rapidly in postpartum hosts. Here we report on PD-L1 expression by lymphatic endothelial cells and CD11b+ cells in the microenvironment of postpartum tumors, which is accompanied by an increase in PD-1 expression by T cells. Additionally, we observed increases in PD-L1 and PD-1 in whole mammary tissues during postpartum mammary gland involution; a known driver of postpartum tumor growth, invasion, and metastasis in pre-clinical models. Importantly, implantation of murine mammary tumor cells during postpartum mammary gland involution elicits a CD8+ T cell population that expresses both the co-inhibitory receptors PD-1 and Lag-3. However, upon anti-PD-1 treatment, during postpartum mammary gland involution, the involution-initiated promotional effects on tumor growth are reversed and the PD-1, Lag-3 double positive population disappears. Consequently, we observed an expansion of poly-functional CD8+ T cells that produced both IFN and TNF. Finally, lymphatic vessel frequency decreased significantly following anti-PD-1 suggesting that anti-PD-1/PD-L1 targeted therapies may have efficacy in reducing tumor growth and dissemination in postpartum breast cancer patients.